The Effect of My Simple Show in Writing Recount Text at the Indonesian Junior High School - Wahyu avtiya; Wahyu Taufiq (International Consortium of Education and Culture Research Studies, 2021)
The objectives of this research are to find out whether there is any significant of students in teaching writing recount text between before and after by using My Simple Show and how the student’s perception towards the use of this application in teaching writing recount text. The method used is quantitative by using a pre-experimental design and questionnaire, To get data, the researcher gave a Pre-test, and Post-test to students. Based on the result of the research, there are some research that can be represented. First, there is significance of My Simple Show to write recount text. Second, the students perception of My Simple Show to increase recount text. Based on the result of this research, the researcher hope can help the students to increase writing ability in recount text by using this application, and give more motivation to be creative.